2017
DOI: 10.1177/1440783317740981
|View full text |Cite
|
Sign up to set email alerts
|

Exploring constructions of masculinity on a men’s body-positivity blog

Abstract: Men's experiences with digital media and social networking sites remain relatively underexplored. Here, we analyse the complex ways that men construct, represent and perform masculinity on a men's body-positivity Tumblr blog called Body Positivity for Guys. Drawing on both hegemonic masculinity theory and inclusive masculinity theory' we contribute to current theoretical discussions within the academic literature on masculinities, while extending these prominent debates to new virtual environments. In particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Many women and people of colour have written about the intersections of decreasing homophobia, sexuality and gender (e.g. Brodyn and Ghaziani, 2018; Caruso and Roberts, 2018; Dashper, 2012; Elliot, 2016; Frank, 2008; Ghaziani, 2014; Haltom and Worthen, 2014; Morales, 2018; Ralph and Roberts, 2018; Roberts, 2013, 2018; Worthen, 2014), yet not one of them is cited. Given Bridges’ (2019) laudable aim for masculinities studies to become more diverse not least through citation practices, it is inexplicable that the only citations they offer related to what they call ‘work within the “inclusive masculinity” framework’ are from two established, white, cis-gendered gay male academics.…”
Section: The Citation Practices Are Biasedmentioning
confidence: 99%
“…Many women and people of colour have written about the intersections of decreasing homophobia, sexuality and gender (e.g. Brodyn and Ghaziani, 2018; Caruso and Roberts, 2018; Dashper, 2012; Elliot, 2016; Frank, 2008; Ghaziani, 2014; Haltom and Worthen, 2014; Morales, 2018; Ralph and Roberts, 2018; Roberts, 2013, 2018; Worthen, 2014), yet not one of them is cited. Given Bridges’ (2019) laudable aim for masculinities studies to become more diverse not least through citation practices, it is inexplicable that the only citations they offer related to what they call ‘work within the “inclusive masculinity” framework’ are from two established, white, cis-gendered gay male academics.…”
Section: The Citation Practices Are Biasedmentioning
confidence: 99%
“…The first is to exclude the visual material (i.e., pictures) completely and either describe it alongside the textual material such as caption, hashtags, and comments (Tiidenberg, 2018a) or to aggregate the textual material into critical themes (Friedman, 2018). The second strategy is to use the visual material but cover identifying features, such as eyes, with a black box/censor bar in an attempt to protect users’ identity (Caruso & Roberts, 2017). We welcome these efforts to not simply assume public availability but also believe that they have certain limitations.…”
Section: Research Ethics and Social Media Researchmentioning
confidence: 99%
“…This level of emotional vulnerability is in direct contrast to traditional masculinity norms that require men to be stoic and resist sharing feelings and emotions, particularly with another man (Courtenay, 2000). Emotional intimacy was identified in 23 of the studies (Adams, 2011;Anderson, 2008Anderson, , 2011Anderson, , 2012Anderson & McGuire, 2010;Blanchard et al, 2017;Brandth & Kvande, 2018;Caruso & Roberts, 2018;Fine, 2019;Finn & Henwood, 2009;Gottzén & Kremer-Sadlick, 2012;Henwood & Procter, 2003;Jóhannsdóttir & Gíslason, 2018;Johansson, 2011;Lee & Lee, 2018;Magrath & Scoats, 2019;McCormack, 2011;McCormack, 2014;Morales & Caffyn-Parsons, 2017;Morris & Anderson, 2015;Roberts et al, 2017;Robinson et al, 2018;White & Hobson, 2017). Anderson (2011) described participants hugging and comforting each other openly when sad or upset.…”
Section: Emotional Intimacymentioning
confidence: 99%
“…The Global Theme of Inclusivity relates to the participants' acceptance of homosexuality, decreasing levels of homophobia, as well as decreasing levels of misogyny, and a general desire for gender equality. Twenty-four of the 33 studies reported that the participants displayed decreased levels of homophobia (Adams, 2011;Anderson, 2008Anderson, , 2011Anderson, , 2012Anderson et al, 2019;Anderson & McCormack, 2015;Anderson & McGuire, 2010;Blanchard et al, 2017;Caruso & Roberts, 2018;Drummond et al, 2014;Fine, 2019;Hall et al, 2012;Jarvis, 2013;Jóhannsdóttir & Gíslason, 2018;Magrath & Scoats, 2019;McCormack, 2011McCormack, , 2014Morales & Caffyn-Parsons, 2017;Morris & Anderson, 2015;Pfaffendorf, 2017;Roberts et al, 2017;Robinson et al, 2018;Scoats, 2017;White & Hobson, 2017). This ranged from what was described as shifting attitudes toward homosexuality (Jarvis, 2013), to the complete absence of homophobia (Morales & Caffyn-Parsons, 2017).…”
Section: Inclusivitymentioning
confidence: 99%
See 1 more Smart Citation